Chip-type ceramic semiconductor electronic components

By integrating hard particles at the interface between the first and second external electrodes, the adhesion strength is enhanced, addressing the peeling issue in small ceramic semiconductor components and ensuring a stable electrical connection.

JP7616230B2Active Publication Date: 2025-01-17MURATA MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022550410
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-17
Filing Date
2021-08-11
Publication Date
2025-01-17
Estimated Expiration
2041-08-11

AI Technical Summary

Technical Problem

In small chip-type ceramic semiconductor electronic components, the adhesion strength between the first and second external electrodes decreases, leading to a risk of peeling at the interface, particularly for dimensions smaller than 1005M.

Method used

Incorporating hard particles made of a material harder than the first external electrode at the interface between the first and second external electrodes, which act as anchors to enhance adhesion.

Benefits of technology

The anchoring effect of the hard particles improves the adhesion strength between the electrodes, preventing peeling and ensuring a stable electrical connection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616230000003
    Figure 0007616230000003
  • Figure 0007616230000004
    Figure 0007616230000004
  • Figure 0007616230000005
    Figure 0007616230000005
Patent Text Reader

Abstract

Provided is a chip-type ceramic semiconductor electronic component 10 in which the interface B between a first external electrode 3 and a second external electrode 4 does not easily peel, even when the dimensions are small. This chip-type ceramic semiconductor electronic component 10 comprises a ceramic element 2 that includes a ceramic semiconductor and that has first surfaces 21 and second surfaces 22 in contact with the first surfaces 21, first external electrodes 3 provided on the first surfaces 21 of the ceramic element 2, and second external electrodes 4 that cover the first external electrodes 3 and that extend to the second surfaces 22 of the ceramic element 2, the area of a first surface 35 of the first external electrodes 3 being less than 0.17 mm2, and hard particles 7 made of a material harder than the first external electrodes 3 being positioned at the interfaces B between the first external electrodes 3 and the second external electrodes 4.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to chip-type ceramic semiconductor electronic components such as thermistors, including positive temperature coefficient (PTC) thermistors and negative temperature coefficient (NTC) thermistors, varistors, and capacitors. [Background technology]

[0002] In recent years, with the development of electronics technology, there has been a demand for reducing the variation in resistance value in chip-type ceramic semiconductor electronic components.

[0003] Patent Document 1 discloses a chip-type ceramic semiconductor electronic component including a ceramic body containing a ceramic semiconductor, a pair of first external electrodes formed on both end faces of the ceramic body, and a pair of second external electrodes formed to cover the first external electrodes and extend to part of the side faces of the ceramic body. The second external electrodes include a conductive material and a thermosetting resin cured at a temperature of 500°C or less. In the chip-type ceramic semiconductor electronic component disclosed in Patent Document 1, the second external electrode is formed using a resin material that can be hardened at a temperature lower than the temperature during heat treatment such as baking, thereby making it possible to suppress oxidation and / or segregation of metal elements contained in the first external electrode, and as a result, it is possible to reduce the variation in the rate of change in resistance value before and after mounting in the chip-type ceramic semiconductor electronic component. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 042884 Summary of the Invention [Problem to be solved by the invention]

[0005] In the chip-type ceramic semiconductor electronic component disclosed in Patent Document 1, as the size becomes smaller, the contact area between the first external electrode and the second external electrode becomes smaller, and the adhesive strength between the first external electrode and the second external electrode is likely to decrease. In particular, in a chip-type ceramic semiconductor electronic component having dimensions smaller than the dimensional standard 1005M (JIS C 5101-21:2014, Appendix A), there is a concern that the interface between the first external electrode and the second external electrode may peel off. An object of the present invention is to provide a chip-type ceramic semiconductor electronic component in which the interface between the first external electrode and the second external electrode is not easily peeled off even when the component is small in size. [Means for solving the problem]

[0006] According to one aspect of the present invention, a ceramic body including a ceramic semiconductor and having a first surface and a second surface in contact with the first surface; a first external electrode provided on the first surface of the ceramic body; a second external electrode covering the first external electrode and extending to the second surface of the ceramic body; A chip-type ceramic semiconductor electronic component comprising: The area of ​​the first surface of the first external electrode is 0.17 mm 2 is less than The chip-type ceramic semiconductor electronic component has hard particles made of a material harder than the first external electrode disposed at the interface between the first external electrode and the second external electrode. Effect of the Invention

[0007] According to the present invention, the hard particles arranged at the interface between the first and second external electrodes exert an anchor effect, improving the bonding strength between the first and second external electrodes. As a result, even in a chip-type ceramic semiconductor electronic component with dimensions smaller than the dimensional standard 1005M (JIS C 5101-21:2014, Appendix A), the interface between the first and second external electrodes can be made less prone to peeling. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic top view of a chip-type ceramic semiconductor electronic component according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic partial cross-sectional view of the chip-type ceramic semiconductor electronic component shown in FIG. [Diagram 3] 3 is a schematic enlarged view of a first external electrode and a second external electrode provided on one end surface of the ceramic body in the chip-type ceramic semiconductor electronic component shown in FIG. [Figure 4] FIG. 4 is a schematic enlarged view of a first external electrode of the chip-type ceramic semiconductor electronic component shown in FIG. [Diagram 5] FIG. 5 is a schematic partial cross-sectional view of a chip-type ceramic semiconductor electronic component according to a second embodiment of the present invention. [Figure 6] FIG. 6 is a schematic perspective view for explaining the dimensions of the chip defined by the JIS standard. [Figure 7] FIG. 7 is a graph showing the change in minimum bonding strength versus end face area of ​​the ceramic body, measured in the examples. [Figure 8] FIG. 8 is a graph showing the change in minimum adhesive strength versus the hard particle content, measured in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A chip-type ceramic semiconductor electronic component according to an embodiment of the present invention has a configuration in which a first external electrode and a second external electrode are laminated on the end faces of a ceramic body, and is characterized in that hard particles made of a material harder than the first external electrode are arranged at the interface between the first external electrode and the second external electrode. The hard particles arranged at the interface between the first external electrode and the second external electrode exert an anchor effect, thereby improving the bonding strength between the first external electrode and the second external electrode and making it possible to suppress peeling at the interface between the first external electrode and the second external electrode. This is particularly suitable for small chip-type ceramic semiconductor electronic components in which this effect is prominent. Hereinafter, an embodiment will be described with reference to the drawings.

[0010] <First embodiment> Fig. 1 is a schematic top view of a chip-type ceramic semiconductor electronic component 10 according to a first embodiment of the present invention. Fig. 2 is a schematic partial cross-sectional view showing cross sections of a first external electrode 3 and a second external electrode 4 in the chip-type ceramic semiconductor electronic component 10 shown in Fig. 1. Fig. 3 is a schematic enlarged view of the first external electrode 3 and the second external electrode 4 provided on one end surface 21 of a ceramic body 2 in the chip-type ceramic semiconductor electronic component 10. A chip-type ceramic semiconductor electronic component 10 comprises a ceramic body 2, a pair of first external electrodes 3 provided on opposing end faces 21, 21 of the ceramic body 2, and a pair of second external electrodes 4 covering the first external electrodes 3 and extending to side faces 22 of the ceramic body 2. The end faces 21, 21 are first faces of the ceramic body 2. The side faces 22 are second faces of the ceramic body 2 that contact the end faces 21, 21, which are the first faces.

[0011] 3, the chip-type ceramic semiconductor electronic component 10 further includes hard particles 7 made of a material harder than the first external electrode 3. The hard particles 7 are disposed at an interface B between the first external electrode 3 and the second external electrode 4. The hard particles 7 function as an anchor that bonds the first external electrode 3 and the second external electrode 4 together, thereby increasing the bonding strength between the first external electrode 3 and the second external electrode 4. This makes it possible to suppress peeling at the interface between the first external electrode 3 and the second external electrode 4. The bonding strength between the first external electrode 3 and the second external electrode 4 is, in other words, the bonding strength at the interface B between the first external electrode 3 and the second external electrode 4.

[0012] The higher the occupancy rate of the interface B with the first external electrode 3 by the hard particles 7, the more improved the anchor effect caused by the hard particles 7. The anchor effect caused by the hard particles 7 is the effect of the hard particles 7 functioning as anchors joining the first external electrode 3 and the second external electrode 4 and / or the effect of the components of the second external electrode 4 entering into minute gaps between the first external electrode 3 and the hard particles 7, causing the components of the second external electrode 4 to function as anchors.

[0013] For example, it is preferable that the volume of the first external electrode 3 and the volume of the hard particles 7 satisfy the following formula (1). 1.03≧P / V≧0.25 (1) Where: P is the volume of the hard particles 7 . V is the volume of the first external electrode 3 included in the range from the interface B between the first external electrode 3 and the second external electrode 4 to a depth D (FIG. 4) toward the inside of the first external electrode 3. The depth D is determined by 1.2× the average grain size of the hard particles.

[0014] The "average particle size" of the hard particles 7 is determined as follows. An SEM image including the interface B between the first external electrode 3 and the second external electrode 4 is taken. In the obtained SEM image, of the hard particles 7 contained within an area defined as 31 μm × 42 μm, the hard particles 7 having a maximum dimension of 0.05 μm or more and 5.0 μm or less are subjected to image processing to determine the circle-equivalent diameter, and the average value of the circle-equivalent diameters is regarded as the average particle size of the hard particles 7.

[0015] The volume P of the hard particles 7 and the volume V of the first external electrode 3 up to the depth D are obtained by the following method. FIG. 6 is a schematic perspective view for explaining the dimensions of a chip defined in the JIS standard. With reference to FIG. 6, when the dimensions of a chip-type ceramic semiconductor electronic component 10 are L (length)×W (width)×T (thickness), a cross section of the chip-type ceramic semiconductor electronic component 10 that is parallel to the WL plane (horizontal plane in FIG. 6) or the LT plane (longitudinal vertical plane in FIG. 6) and passes through approximately the center of the chip-type ceramic semiconductor electronic component 10 is exposed by a method such as polishing or cutting. In the exposed cross section, the vicinity of the interface B between the first external electrode 3 and the second external electrode 4 is measured by SEM-EDX (scanning electron microscope / energy dispersive X-ray spectroscopy). At this time, a quantitative analysis is performed by specifying the range from the interface B to the depth D of the first external electrode 3. The elements constituting the first external electrode 3 (e.g., Ag) and the elements constituting the hard particles 7 (e.g., Al when the hard particles are Al) are measured. 2 O 3 The molar content of each of these elements is calculated as Ag and Al. 2 O 3 The volume of the hard particles 7 is calculated as P (μm 2 ) and the volume V (μm 2 ) is required.

[0016] By satisfying formula (1), the anchor effect caused by the hard particles 7 becomes prominent, and the effect of suppressing peeling between the first external electrode 3 and the second external electrode 4 at the interface B can be improved. In addition, the electrical connection between the first external electrode 3 and the second external electrode 4 can be sufficiently ensured. The lower limit of P / V defined by formula (1) is more preferably 0.40 or more, and particularly preferably 0.50 or more, and the upper limit of P / V is more preferably 0.90 or less, and particularly preferably 0.80 or less.

[0017] In another example, it is preferable that the area occupied by the hard particles 7 at the interface B between the first external electrode 3 and the second external electrode 4 satisfies the following formula (2). 0.90 ≥ PS / (IF S +P S )≧0.20 (2) Where: P S is the area occupied by the hard particles 7 at the interface B between the first external electrode 3 and the second external electrode 4. IF S is the area where the first external electrode 3 and the second external electrode 4 are in contact with each other at the interface B between the first external electrode 3 and the second external electrode 4.

[0018] Area P occupied by hard particles 7 S and the contact area IF S is determined by the following method. Referring to Fig. 6, when the dimensions of the chip-type ceramic semiconductor electronic component 10 are L (length) x W (width) x T (thickness), a cross section of the chip-type ceramic semiconductor electronic component 10 that is parallel to the WL plane (horizontal plane in Fig. 6) or LT plane (vertical plane in the longitudinal direction in Fig. 6) and passes through approximately the center of the chip-type ceramic semiconductor electronic component 10 is exposed by a method such as polishing or cutting. In the exposed cross section, the vicinity of the interface B between the first external electrode 3 and the second external electrode 4 is observed with an SEM (scanning electron microscope). In the SEM image, a straight line is drawn along the interface B, and the length that this straight line passes through the hard particles is defined as "P L ", and the length of contact between the first external electrode 3 and the second external electrode 4 is "IF L " The total length of the straight line is "IF L +P L The same measurement is carried out five times at different positions in the same SEM image. The "P L " is calculated by dividing the total area occupied by the hard particles 7 by "P S ” and the “IF” obtained from those measurements L " is calculated as the contact area "IF S " is deemed to be the case.

[0019] By satisfying formula (2), the anchor effect caused by the hard particles 7 becomes prominent, and the effect of suppressing peeling between the first external electrode 3 and the second external electrode 4 at the interface B can be improved. In addition, the electrical connection between the first external electrode 3 and the second external electrode 4 can be sufficiently ensured. P defined by formula (2) S / (IF S +P S The lower limit of P is more preferably 0.25 or more, and particularly preferably 0.30 or more. S / (IF S +P S The upper limit of the ratio is more preferably 0.50 or less, and particularly preferably 0.40 or less.

[0020] (First external electrode 3) The pair of first external electrodes 3 are provided on opposing end faces 21, 21 of the ceramic body 2. In this specification, the two faces perpendicular to the longitudinal direction of the ceramic body 2 are referred to as "end faces" 21, and the four faces perpendicular to both end faces 21 are referred to as "side faces" 22. The first external electrodes 3 may be provided on a part or the entirety of the end faces 21 of the ceramic body 2. The first external electrodes 3 have ohmic properties with respect to the ceramic body 2. The first external electrode 3 includes one selected from the group consisting of Ag, Ni, Cr, Ti, Zn, V, and W, for example.

[0021] The area of ​​the end face 35 of the first external electrode 3 is 0.17 mm 2 The end face 35 is the first face of the first external electrode 3. The area of ​​the end face 35 is less than 0.17 mm 2 When the area of ​​the end face 35 of the first external electrode 3 is less than 0.06 mm2, the adhesive strength between the first external electrode 3 and the second external electrode 4 can be improved by disposing the hard particles 7 at the interface B, compared to a case where no hard particles are disposed. 2 In the chip-type ceramic semiconductor electronic component 10 described below, the effect of improving the adhesive strength between the first external electrode 3 and the second external electrode 4 by the hard particles 7 is remarkable, and therefore the chip-type ceramic semiconductor electronic component 10 is particularly suitable for application of the present invention.

[0022] (hard particles 7) The hard particles 7 are made of a material that is harder than at least the first external electrode 3. This makes it easier to make the hard particles 7 partially embedded in the surface of the first external electrode 3 after the first external electrode 3 is provided. The hard particles 7 preferably include particles made of any one of materials selected from the group consisting of alumina, zirconium oxide, and silicon carbide. These materials are hard and widely used as abrasives in barrel polishing, and therefore can be easily used as the hard particles 7 of the present invention.

[0023] (Second external electrode 4) The pair of second external electrodes 4 cover the first external electrodes 3 and extend to the side surfaces 22 of the ceramic body 2. In particular, the second external electrodes 4 preferably include a resin electrode layer containing a conductive material and a resin. The resin electrode layer is provided by hardening a resin electrode paste having fluidity. When the second external electrode 4 is provided, the first external electrode 3 is provided first, then the surface of the first external electrode 3 is partially filled with the hard particles 7, and then the resin electrode paste is applied so as to cover the surface of the first external electrode 3 and the hard particles 7 partially protruding from the surface of the first external electrode 3. There are fine gaps between the first external electrode 3 and the hard particles 7, and the resin component of the resin electrode paste permeates the fine gaps. When the resin electrode paste is hardened, the resin component that has permeated the fine gaps is also hardened. The hardened resin component that has permeated the fine gaps functions as an anchor that firmly bonds the second external electrode 4 to the first external electrode 3, so that the adhesive strength between the first external electrode 3 and the second external electrode 4 can be further increased. Therefore, peeling at the interface between the first external electrode 3 and the second external electrode 4 can be further suppressed.

[0024] The conductive material used in the resin electrode layer may be, for example, metal particles containing one or more of Ag, AgPd, Cu, etc. The average particle size of the metal particles used as the conductive material is preferably about 1.0 to 15 μm. The resin used in the resin electrode layer is preferably a thermosetting resin, such as an epoxy resin, a phenol resin, etc. The thermosetting resin may be used alone or in combination of two or more kinds.

[0025] (Ceramic body 2) The ceramic body 2 contains a ceramic semiconductor. The type of ceramic semiconductor is selected according to the type of desired chip-type ceramic semiconductor electronic component 10 (PTC thermistor, NTC thermistor, varistor, capacitor, etc.). For example, in the case of a PTC thermistor having a positive resistance-temperature characteristic, the ceramic body 2 contains an N-type semiconductor having a positive resistance-temperature characteristic as a main component. Examples of N-type semiconductors include ((Ba, Pb, Sr, Ca) 0.0096 Er 0.004 )TiO 3 It is.

[0026] [Manufacturing method] An example of a method for manufacturing the chip-type ceramic semiconductor electronic component 10 of the first embodiment will be described below. Note that a person skilled in the art who has access to the disclosure of the present application may arrive at a different method for manufacturing the chip-type ceramic semiconductor electronic component 10 of the first embodiment based on the description.

[0027] (1. Preparation of ceramic body 2) First, a mixed raw material is prepared by weighing out a ceramic raw material having a desired composition and, if necessary, other additives (semiconducting agents, property improving agents, sintering aids, etc.) in predetermined amounts as the raw materials for the ceramic body 2. Pure water is added to the mixed raw material, and the mixture is wet mixed and pulverized in a ball mill. The pulverized mixture obtained is calcined to obtain calcined powder. An organic binder, a dispersant, and pure water are added to the calcined powder obtained, and the mixture is mixed in a ball mill to obtain granules. The granules obtained are molded to form green sheets, which are then debindered and fired in air to obtain the ceramic body 2.

[0028] (2. Formation of First External Electrode 3) The first external electrode 3 is formed on the end faces 21, 21 of the ceramic body 2. The first external electrode 3 can be formed by a thin film formation method such as sputtering or vapor deposition. In particular, it is preferable to form the first external electrode 3 by sputtering.

[0029] (3. Polishing of ceramic body 2) After the first external electrodes 3 are formed, the ceramic body 2 is subjected to barrel polishing. In the barrel polishing, an abrasive made of the same material as the hard particles 7 is used. The barrel polishing removes the ridges of the ceramic body 2, and fixes a part of the abrasive (small particles or pieces of the abrasive) in a partially embedded state on the surface of the first external electrode 3. The abrasive partially embedded and fixed on the surface of the first external electrode 3 functions as hard particles 7. In many cases, the hard particles 7 have a particle size significantly smaller than the median particle size of the abrasive used. For example, even when an abrasive with a median particle size of 40 to 60 μm is used, the average particle size of the hard particles 7 is small, for example, 0.1 μm or more and 1.0 μm or less. This is because, in the case of an abrasive with a large particle size, the contact area with the surface of the first external electrode 3 is large, and therefore, it is considered that the stress applied by the barrel polishing is not sufficient to obtain the pressure required for the abrasive to be partially embedded in the surface of the first external electrode 3. On the other hand, it is presumed that the small particle size microparticles or fragments of the abrasive contained in the abrasive have a small contact area with the surface of the first external electrode 3, and therefore the stress applied by barrel polishing provides the pressure necessary for them to become partially embedded in the surface of the first external electrode 3, and therefore they can function as hard particles 7.

[0030] (4. Formation of Second External Electrode 4) After the ceramic body 2 is polished, the second external electrode 4 is formed. When the second external electrode 4 is made of a resin electrode layer containing a conductive material and a resin, a resin electrode paste is prepared by mixing, for example, 69% by weight to 90% by weight of a conductive material, 9% by weight to 30% by weight of a thermosetting resin, and 1% by weight to 5% by weight of a diluent. The end faces 21 and parts of the side faces 22 of the ceramic body 2 are immersed in the resin electrode paste bath. As a result, the resin electrode paste covers the first external electrode 3 and extends to the side faces 22 of the ceramic body 2. After the ceramic body 2 is pulled out of the resin electrode paste bath, a hardening process is performed to form the second external electrode 4.

[0031] <Second embodiment> The chip-type ceramic semiconductor electronic component of the second embodiment differs from the first embodiment in that the first external electrode and the second external electrode both have a multi-layer structure, but is similar to the first embodiment in other respects. With reference to FIG. 5, the following mainly describes the first external electrode 30 and the second external electrode 40, which are differences from the first embodiment.

[0032] (First external electrode 30) The first external electrode 30 has a multilayer structure including a first electrode layer 31 in contact with the ceramic body 2 and in ohmic contact with the ceramic body 2, and a second electrode layer 32 provided as the outermost layer furthest from the ceramic body 2 and in contact with the second external electrode 40. As shown in Fig. 5, the first external electrode 30 may further include a third electrode layer 33 between the first electrode layer 31 and the second electrode layer 32.

[0033] The first electrode layer 31 is selected from a material that makes ohmic contact with the ceramic body 2. For example, the first electrode layer 31 includes one selected from the group consisting of Cr, Zn-Ag, Ti, W, Zn, and V. The second electrode layer 32 is formed outside the first electrode layer 31 and the second electrode layer 32. It may have a function of suppressing oxidation of the first electrode layer 31 and the second electrode layer 32 and protecting them from external forces. The second electrode layer 32 includes one selected from the group consisting of Ag, Ni, Cr, Ti, Zn, V, and W.

[0034] The third electrode layer 33 may be provided to improve adhesion between the first electrode layer 31 and the second electrode layer 32. It is preferable that a material suitable for the third electrode layer 33 is appropriately selected in consideration of adhesion with the material of the first electrode layer 31 and the material of the second electrode layer 32. For example, the third electrode layer 33 may contain Ni and one or more selected from the group consisting of Cu, Cr, and V. An example of a combination of materials constituting the multilayer structure of the first electrode layer 31-the third electrode layer 33-the second electrode layer 32 is Cr-NiCu-Ag.

[0035] (Second external electrode 40) The second external electrode 40 has a multilayer structure including a resin electrode layer 50 containing a conductive material and a resin, and two metal electrode layers 51 and 52 covering the resin electrode layer 50 . The resin electrode layer 50 is similar to the resin electrode layer described in the first embodiment. The two metal electrode layers 51 , 52 include a first metal electrode layer 51 covering the surface of the resin electrode layer 50 , and a second metal electrode layer 52 covering the surface of the first metal electrode layer 51 .

[0036] The first metal electrode layer 51 preferably contains at least one of Ni and Cu. The first metal electrode layer 51 serves to prevent moisture from escaping from inside the resin electrode layer 50 when the chip-type ceramic semiconductor electronic component 11 is mounted. The first metal electrode layer 51 also serves to prevent moisture from the surrounding environment from penetrating into the resin electrode layer 50. The second metal electrode layer 52 preferably contains Sn. The second metal electrode layer 52 can improve the wettability of the solder of the second external electrode 40 when the chip-type ceramic semiconductor electronic component 11 is mounted. In the example of FIG. 5, the metal electrode layers 51 and 52 are made up of two layers, but only one of them may be included.

[0037] The hard particles 7 are arranged at the interface between the first external electrode 30 and the second external electrode 40, more specifically, at the interface B2 between the second electrode layer 32, which is the outermost layer of the first external electrode 30, and the resin electrode layer 50 of the second external electrode 40. The hard particles 7 function as an anchor that bonds the second electrode layer 32 of the first external electrode 30 and the resin electrode layer 50 of the second external electrode 40, and therefore can increase the bonding strength between the second electrode layer 32 and the resin electrode layer 50. Therefore, peeling at the interface between the second electrode layer 32 and the resin electrode layer 50 can be suppressed.

[0038] The hard particles 7 are made of a material harder than the second electrode layer 32 which is the outermost layer of the first external electrode 30. This makes it easier to make the hard particles 7 partially embedded in the surface of the second electrode layer 32 after the second electrode layer 32 of the first external electrode 30 is provided.

[0039] [Manufacturing method] Hereinafter, a method for manufacturing the chip-type ceramic semiconductor electronic component 11 according to the second embodiment, in particular a method for manufacturing the first external electrode 30 and the second external electrode 40, will be described.

[0040] (1. Preparation of ceramic body 2) Since this is similar to the first embodiment, the description will be omitted.

[0041] (2. Formation of the First External Electrode 30) The first external electrode 30 is formed by successively forming the first electrode layer 31, the third electrode layer 33, and the second electrode layer 32 on the end faces 21, 21 of the ceramic body 2. The first electrode layer 31, the third electrode layer 33, and the second electrode layer 32 can be formed by a thin film formation method such as a sputtering method or vapor deposition. In particular, it is preferable to form them by a sputtering method.

[0042] (3. Polishing of ceramic body 2) After the first external electrode 30 is formed, the ceramic body 2 is subjected to barrel polishing. The conditions for barrel polishing are the same as those in the first embodiment, and therefore a description thereof will be omitted. Barrel polishing removes the ridges of the ceramic body 2, and also fixes some of the abrasive (microparticles with a small particle size or pieces of the abrasive) in a partially embedded state to the surface of the first external electrode 30, i.e., the surface of the second electrode layer 32. The abrasive fixed in a partially embedded state to the surface of the second electrode layer 32 functions as hard particles 7. The material, particle size, etc. of the hard particles 7 are the same as those in the first embodiment, so a description thereof will be omitted.

[0043] (4. Formation of Second External Electrode 40) After polishing the ceramic body 2, the second external electrode 40 is formed. The resin electrode layer 50 is formed so as to cover the first external electrode 3. The method for forming the resin electrode layer 50 is similar to the method for forming the resin electrode layer described in the first embodiment, and therefore the description will be omitted. Furthermore, a first metal electrode layer 51 and a second metal electrode layer 52 are formed in this order so as to cover the resin electrode layer 50. The first metal electrode layer 51 and the second metal electrode layer 52 are preferably formed by electrolytic plating. EXAMPLES

[0044] (1) Preparation of test samples As a test sample of a chip-type ceramic semiconductor electronic component, a chip PTC having the structure shown in FIG. 5 was fabricated.

[0045] First, as a ceramic raw material, BaCO 3 , TiO 2 , PbO, SrCO 3 , CaCO 3 Ceramic raw materials such as Er 2 O 3 The semiconductor agent is Er. 2 O 3 Alternatively, an oxide of at least one rare earth element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu may be used instead of the above. In addition to the above-mentioned ceramic raw materials and semiconducting agent, Mn 2 O 3 and other property improving agents, and SiO 2A sintering aid such as sintering agent may be used. The weighed raw materials are charged into a ball mill together with grinding media such as partially stabilized zirconia (PSZ) (hereinafter also referred to as PSZ balls) and pure water, and wet mixed and ground. The mixture obtained is calcined at a predetermined temperature (for example, 1000 to 1200°C) to obtain calcined powder. An organic binder, a dispersant, and water are added to the calcined powder obtained, and the mixture is mixed with PSZ balls for a predetermined time to be granulated. The obtained granulated material is molded to form green sheets, which are then debindered and then fired in the atmosphere at a predetermined temperature (1200 to 1400°C) to form ceramic bodies 2 having various dimensions. The dimensions of the ceramic body 2 are shown in Table 1. 5000 ceramic bodies 2 were produced for each dimension. A first external electrode 30 having a multilayer structure was formed on the end faces 21, 21 of the obtained ceramic body 2 by a sputtering method. The materials of the first electrode layer 31-the third electrode layer 33-the second electrode layer 32 of the first external electrode 30 were Cr-NiCu-Ag, respectively, and the thickness of each electrode layer was 0.3 μm-1.0 μm-1.3 μm.

[0046] After the first external electrode 30 was formed, the ridges of the ceramic body 2 were removed by barrel polishing. At this time, alumina particles having a median particle size of 40 to 60 μm were added to the pot as an abrasive in an amount (140 g / pot) that was twice the usual amount (70 g / pot).

[0047] Thereafter, a resin electrode paste for forming the resin electrode layer 50 of the second external electrode 40 is prepared. The resin electrode paste is a resin-curing Ag paste, which is prepared by mixing 70 to 90% by weight of a conductive material such as Ag, AgPd, or Cu, 10 to 30% by weight of a thermosetting resin such as an epoxy resin or a phenol resin, and 1 to 5% of a diluent. The end face 21 and a part of the side face 22 of the ceramic body 2 are immersed in a resin electrode paste bath, and then the ceramic body is pulled out of the resin electrode paste bath and coated with the resin electrode paste. The resin in the resin electrode paste is cured by heat treatment to form the resin electrode layer 50. Furthermore, a first metal electrode layer 51 made of Ni covering the resin electrode layer 50 and a second metal electrode layer 52 made of Sn are formed by electrolytic plating to obtain a test sample.

[0048] The sizes of the test samples shown in Table 1 were 0402M, 0603M, 1005M, and 1608M, in accordance with the standards stipulated in JIS C 5101-21:2014, Appendix A. The dimensions L (length) × W (width) × T (thickness) (see FIG. 6) of the ceramic body 2 included in the test sample of each size were as shown in the following Table 1. Table 1 also shows the area of ​​the end face of the ceramic body 2 (WT area) and the area of ​​the end face of the first external electrode (WT area), calculated from W (width) and T (thickness).

[0049] [Table 1]

[0050] The obtained test sample was mounted on a mounting board and subjected to an adhesion test. The adhesion test was conducted in accordance with 4.28 of JIS C 2570-1 "Directly heated NTC thermistors - Part 1: General rules" 2006 edition. Depending on the size of the sample, the experimental conditions of 5N / holding time 10±1 seconds, which is the standard value, may cause the ceramic element to break during the test, causing cracks to form at the contact point with the pressing jig, and only a G (good) or NG (bad) judgment can be made. For this reason, in order to quantitatively compare the strength, the applied stress was gradually increased until the test sample broke, and the stress at the point when the test sample broke was taken as the adhesion strength of that sample. Note that here, the point when the stress of the displacement transition reaches its maximum is judged as the breakage.

[0051] For each size, 3 lots of 10 test samples (30 in total) were prepared and tested. First, an adhesion test was conducted on the 10 test samples in the first lot to obtain the minimum adhesion strength. Next, an adhesion test was conducted on the 10 test samples in the second lot to obtain the minimum adhesion strength. Then, an adhesion test was conducted on the 10 test samples in the third lot to obtain the minimum adhesion strength. The average of the three minimum adhesion strength values ​​thus obtained and the error bars of the maximum and minimum values ​​were plotted (Figure 7). The unit of the vertical axis is N (Newton).

[0052] 5,000 comparative samples were prepared and the adhesion strength was measured. The comparative samples were prepared in the same manner as the test samples, except that alumina particles having a median particle size of 40 to 60 μm were added to the pot as the abrasive in the barrel polishing after the formation of the first external electrode in the usual amount (70 g / pot). The WT area of ​​the ceramic body 2 was 0.25 mm 2 or more (WT area of ​​the first external electrode is 0.17 mm 2 In the above cases, no significant difference was observed in the minimum bond strength between the test sample (with hard particles 7) and the comparative sample (without substantially hard particles 7), but when the WT area of ​​the ceramic body 2 was 0.25 mm 2 Less than (WT area of ​​the first external electrode is 0.17 mm 2 In particular, when the WT area of ​​the ceramic body 2 was 0.09 mm or less, a significant difference was observed. 2(The WT area of ​​the first external electrode is 0.06 mm 2 ) and 0.04 mm 2 (The WT area of ​​the first external electrode is 0.03 mm 2 ) the adhesive strength of the comparative sample was significantly reduced, but by providing the hard particles 7, the adhesive strength could be significantly improved.

[0053] The fracture mode refers to the location where fracture occurs, and is generally the part of the chip with the weakest strength. The fracture mode of the comparison sample was fracture at the interface between the first and second external electrodes, but the fracture mode of the test sample was not fracture at the interface between the first and second external electrodes 30 and 40, and all fracture occurred in the ceramic body 2. The fracture mode was confirmed by observing the fractured locations with a SEM (scanning electron microscope). From the results of Example 1, it was confirmed that the adhesive strength between the first external electrode 30 and the second external electrode 40 could be made stronger than the strength of the ceramic body. EXAMPLES

[0054] By changing the amount of abrasive added during barrel polishing, 5,000 test samples of size 0603M (Table 1) were produced in the same manner as in Example 1. The amount of abrasive is shown in Table 2. In addition, No. 2 in Table 2 is a comparative sample having a conventional structure, and No. 3 is a test sample prepared in Example 1. The obtained test samples were examined for the amount of hard particles 7 present at the interface between the first external electrode and the second external electrode, and the adhesion strength between the first external electrode 30 and the second external electrode 40.

[0055] The content (volume P) of the hard particles 7 and the amount (volume V) of the first external electrode 30 up to the depth D were determined as follows. The test sample was sealed with resin, and a cross section parallel to the WL plane (horizontal plane in FIG. 6) or LT plane (vertical plane to the longitudinal direction in FIG. 6) and passing through approximately the center of the test sample was exposed by polishing. In the exposed cross section, the vicinity of the interface B2 between the first external electrode 30 and the second external electrode 40 was measured by SEM-EDX (FlexSEM1000, manufactured by Hitachi High-Technologies Corporation). The measurement conditions were low vacuum mode, backscattered electron image, and 15 kV acceleration voltage.

[0056] At this time, quantitative analysis of elements was performed by EDX on the first external electrode 30 in the range from the interface B2 to a depth of 2.4 μm. Then, it was found that Ag constituting the second electrode 32 of the first external electrode 30 and the hard particles 7 (Al 2 O 3 The molar content of each of the elements Ag and Al was calculated. 2 O 3 The volume of the hard particles 7 is calculated as P (μm 2 ) and the volume of Ag contained in the area from the interface B2 to a depth of 2.4 μm V 0 (μm 2 Here, only the second electrode 32 of the first external electrode 30 contains Ag, so the volume of Ag V 0 (μm 2 ) can be regarded as the volume of the second electrode 32 having a thickness of 1.3 μm. 0 (μm 2 ) of the first external electrode 3 from the interface B2 to the depth D (μm 2 ) Since the average particle size of the hard particles 7 was 1.0 μm, D was 1.2×(average particle size of the hard particles 7)=1.2 μm. V=V 0 ×D / (thickness of second electrode 32) (3) That is, the volume V (μm 2 ) is the volume of Ag V 0 (μm 2)) × 1.2 (μm) / 1.3 (μm).

[0057] [Table 2]

[0058] Five samples were observed for each sample, and the P / V value was calculated. The average P / V value (ave P / V) calculated for the five samples and the error bars of the maximum and minimum values ​​of P / V are plotted on the x-axis of Figure 8.

[0059] The obtained samples were mounted on a mounting board and subjected to an adhesion test under the same conditions as in Example 1. Ten samples were prepared for each size and subjected to the test, and the minimum value of the adhesion test was plotted on the y-axis.

[0060] From the graph in Figure 8, Al 2 O 3 It can be seen that the adhesion strength improved significantly when the Ag average volume ratio (ave P / V) was 0.25 or higher. Regarding the fracture mode, when the ratio was 0.25 or higher, there was no fracture at the interface between the first and second external electrodes, and all fracture occurred in the ceramic body. This shows that the intended adhesion strength at the interface between the first and second external electrodes could be made stronger than the strength of the ceramic body.

[0061] This application claims priority based on Japanese Patent Application No. 2020-156746, filed in Japan on September 17, 2020, the entire contents of which are incorporated herein by reference. [Explanation of symbols]

[0062] 10, 11 Chip-type ceramic semiconductor electronic components 2 Ceramic body 21 First surface (end surface) of ceramic body 22 Second surface (side surface) of ceramic body 3, 30 First external electrode 31 First electrode layer of the first external electrode 32 Second electrode layer of the first external electrode 33 Third electrode layer of the first external electrode 35 First surface (end surface) of first external electrode 4, 40 Second outer electrode 50 Resin electrode layer 51 First metal electrode layer 52 Second metal electrode layer 7 hard particles B, B2: Interface between the first external electrode and the second external electrode

Claims

1. a ceramic body including a ceramic semiconductor and having a first surface and a second surface in contact with the first surface; a first external electrode provided on the first surface of the ceramic body; a second external electrode covering the first external electrode and extending to the second surface of the ceramic body; A chip-type ceramic semiconductor electronic component comprising: The area of ​​the first surface of the first external electrode is 0.17 mm 2 is less than hard particles made of a material harder than the first external electrode are disposed at an interface between the first external electrode and the second external electrode; A chip-type ceramic semiconductor electronic component that satisfies the following formula (1): 1.03 ≧ P / V ≧ 0.25 (1) Where: P is the volume of the hard particles. V is the volume of the first external electrode included in the range from the interface between the first external electrode and the second external electrode to a depth D (= 1.2 x the average particle diameter of the hard particles) toward the inside of the first external electrode.

2. 2. The chip-type ceramic semiconductor electronic component according to claim 1, wherein the first external electrodes include one selected from the group consisting of Ag, Ni, Cr, Ti, Zn, V, and W.

3. The first external electrode is a first electrode layer in contact with the ceramic body; a second electrode layer provided as an outermost layer furthest from the ceramic body and in contact with the second external electrode, 3. The chip-type ceramic semiconductor electronic component according to claim 1, wherein the hard particles are made of a material harder than that of the second electrode layer.

4. 4. The chip-type ceramic semiconductor electronic component according to claim 3, wherein the second electrode layer includes one selected from the group consisting of Ag, Ni, Cr, Ti, Zn, V, and W.

5. 5. The chip-type ceramic semiconductor electronic component according to claim 1, wherein the hard particles include particles made of any one of materials selected from the group consisting of alumina, zirconium oxide, and silicon carbide.

6. 6. The chip-type ceramic semiconductor electronic component according to claim 1, wherein the second external electrode includes a resin electrode layer containing a conductive material and a resin.

7. 7. The chip-type ceramic semiconductor electronic component according to claim 6, wherein the second external electrode further includes a metal electrode layer covering the resin electrode layer.

8. The area is 0.06 mm 2 The chip-type ceramic semiconductor electronic component according to any one of claims 1 to 7, wherein:

Citation Information

Patent Citations

  • Method for manufacturing semiconductor ceramic electronic component

    JP2005327929A

  • Electronic component and method for manufacturing the same

    JP2008028064A

  • Method of manufacturing electronic component

    JP2009049320A

  • Mounting structure of electronic component

    JP2009200421A

  • Chip-type ceramic semiconductor electronic component

    WO2016042884A1